Clinical and radiological assessment of Quadriceps atrophy after knee injury - waleed, mostafa (Karbala Journal of Medicine, 2020)
Background:knee injuries is commom problem , immobilization of the knee during management of acute injury carry risk of muscle atrophy that have negative impact on regaining preinjury level of sterngth. Methods: Prospective cohort study was included 32 patients selected with acute knee injury who presentated within 24 hour, management protocol involove 7 days of immobilization then fellowed by 6 weeks of rehabiliatation programe for qudericepse sterengthening, the evaluation of muscle wasting include clinical assessment of thigh circumfrences and ultrasonography of muscle volume at three different points of time. Results: Measurment showed significant atrophy after 7 days of immobilization with excellent impact on muscle strength after 6 week of rehahibilatation when compared the the injuerd with healthy side. Clinical assessment compared to radiological assessment of muscle atrophy and the comparison of the real thigh circumference and ultrasonography readings of the injured limb between the three measurement phases showed significant differences (p< 0.001). Ultrasound measurement comparison of the thigh circumference reading of the injured limb between the three measurement phases showed no significant differences (p= 0.439). Conclusion: Muscle atrophy can ocuured as early as one week of immobilization after knee injury. Clinical and radiological method can be used effeiently to assess muscle atrophy